PEMANFAATAN MEDIA PEMBELAJARAN DALAM LAYANAN INFORMASI BIMBINGAN KONSELING - Azmatul Khairiah Sari (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2017)
Information service in counseling guidence is common thing for counseling guidence teacher. So that every teacher ought to mastered on managing class, understanding and others. Counseling guidence service as a prosess to learn for the students in order to make the goal. One of the way that teacher do is that by use media in learning.